Effect of different packaging systems and chlorination on the quality and shelf life of green chili (Bangladesh Journal of Agricultural Research, 2013)
The experiment was conducted to evaluate the effect of packaging materials on the quality and shelf life of green chili (Capsicum annuum) using passive modification of modified atmosphere packaging system. The modified atmosphere was created by making perforation in the polypropylene packets. Green chili pre-treated with chlorine water and then packaging in 0.3% perforated polypropylene packet resulted substantial reduction of weight loss and rotting/shriveling. These treatment combinations also considerably retained vitamin C, ß-carotene, moisture content, etc. Under this condition the retention of quality and shelf life of green chili could be extended up to 10 days at ambient condition as compared to non-treated and without packaging. DOI: http://dx.doi.org/10.3329/bjar.v37i4.14397 Bangladesh J. Agril. Res. 37(4): 729-736, December 2012